Daphnetin inhibits proliferation and inflammatory response in human HaCaT keratinocytes and ameliorates imiquimod-induced psoriasis-like skin lesion in mice - Gao, Jintao; Chen, Fangru; Fang, Huanan; Mi, Jing; Qi, Qi; Yang, Mengjuan (Biological research, 2020)
Psoriasis is a common chronic inflammatory skin disease. Keratinocytes hyperproliferation and excessive inflammatory response contribute to psoriasis pathogenesis. The agents able to attenuate keratinocytes hyperproliferation and excessive inflammatory response are considered to be potentially useful for psoriasis treatment. Daphnetin exhibits broad bioactivities including anti-proliferation and anti-inflammatory. This study aims to evaluate the anti-psoriatic potential of daphnetin in vitro and in vivo, and explore underlying mechanisms. HaCaT keratinocytes was stimulated with the mixture of IL-17A, IL-22, oncostatin M, IL-1α, and TNF-α (M5) to establish psoriatic keratinocyte model in vitro. Cell viability was measured using Cell Counting Kit-8 (CCK-8). Quantitative Real-Time PCR (qRT-PCR) was performed to measure the mRNA levels of hyperproliferative marker gene keratin 6 (KRT6), differentiation marker gene keratin 1 (KRT1) and inflammatory factors IL-1β, IL-6, IL-8, TNF-α, IL-23A and MCP-1. Western blotting was used to detect the protein levels of p65 and p-p65. Indirect immunofluorescence assay (IFA) was carried out to detect p65 nuclear translocation. Imiquimod (IMQ) was used to construct psoriasis-like mouse model. Psoriasis severity (erythema, scaling) was scored based on Psoriasis Area Severity Index (PASI). Hematoxylin and eosin (H&E) staining was performed to examine histological change in skin lesion. The expression of inflammatory factors including IL-6, TNF-α, IL-23A and IL-17A in skin lesion was measured by qRT-PCR. Daphnetin attenuated M5-induced hyperproliferation in HaCaT keratinocytes. M5 stimulation significantly upregulated mRNA levels of IL-1β, IL-6, IL-8, TNF-α, IL-23A and MCP-1. However, daphnetin treatment partially attenuated the upregulation of those inflammatory cytokines. Daphnetin was found to be able to inhibit p65 phosphorylation and nuclear translocation in HaCaT keratinocytes. In addition, daphnetin significantly ameliorate the severity of skin lesion (erythema, scaling and epidermal thickness, inflammatory cell infiltration) in IMQ-induced psoriasis-like mouse model. Daphnetin treatment attenuated IMQ-induced upregulation of inflammatory cytokines including IL-6, IL-23A and IL-17A in skin lesion of mice. Daphnetin was able to attenuate proliferation and inflammatory response induced by M5 in HaCaT keratinocytes through suppression of NF-κB signaling pathway. Daphnetin could ameliorate the severity of skin lesion and improve inflammation status in IMQ-induced psoriasis-like mouse model. Daphnetin could be an attractive candidate for future development as an anti-psoriatic agent.